2016
DOI: 10.1073/pnas.1605885113
|View full text |Cite
|
Sign up to set email alerts
|

Mannose receptor induces T-cell tolerance via inhibition of CD45 and up-regulation of CTLA-4

Abstract: The mannose receptor (MR) is an endocytic receptor involved in serum homeostasis and antigen presentation. Here, we identify the MR as a direct regulator of CD8 + T-cell activity. We demonstrate that MR expression on dendritic cells (DCs) impaired T-cell cytotoxicity in vitro and in vivo. This regulatory effect of the MR was mediated by a direct interaction with CD45 on the T cell, inhibiting its phosphatase activity, which resulted in up-regulation of cytotoxic T-lymphocyte-associated Protein 4 (CTLA-4) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 45 publications
2
75
0
1
Order By: Relevance
“…Moreover, MR can interact with other canonical pattern recognition receptors to mediate intracellular signaling. [32][33][34] We found that inhibition of MR by its specific siRNA can block AOS function. The data suggested that AOS might act its function through MR signaling pathway.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, MR can interact with other canonical pattern recognition receptors to mediate intracellular signaling. [32][33][34] We found that inhibition of MR by its specific siRNA can block AOS function. The data suggested that AOS might act its function through MR signaling pathway.…”
Section: Discussionmentioning
confidence: 86%
“…The MR is an endocytic receptor containing eight C-type lectinlike domains (CTLDs) which can bind to glycoconjugates terminated in mannose, fucose, or glucose. We hypothesized that the function of AOS may be through MR. 32,33 Then siRNAs of MR were used in this study in vitro with IPEC-J2 cells (swine intestinal cell line) to explore the mechanism of AOS effects on the recovering of mouse small intestinal. It was very interesting that AOS 10, and 100 μg/ml significantly increased the protein levels of CX43, claudin, DSG2, and APOA1 in IPEC-J2 cells which was constant with the in vivo data in mouse, however, AOS 10, and 100 μg/ml cannot increase the levels of these three proteins in the present of MR siRNA (Fig.…”
Section: Aos Improved Intestinal Cell Functionmentioning
confidence: 99%
“…Blocking the MR modulated the differentiation, maturation, and functions of DCs resulting in a reduced severity of induced autoimmune arthritis [11]. Moreover, deleting or blocking CD206 on DCs decreased the proliferation and cytotoxic activity of urine CD8 + T cells in vitro [10]. The expression of surface molecules on DCs is dynamic and changes according to tissue localization and maturation state.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have further supported the role of MR in controlling inflammation. For instance, MR has been shown to induce T-cell reprogramming and subsequent tolerance via inhibition of CD45 and upregulation of the inhibitory molecule CTLA-4, which was responsible for the impaired cytotoxic activity of T cells [44]. …”
Section: Mannose Receptormentioning
confidence: 99%